«La miglior lezione è sempre quella del buon giudizio»: Monti's notes on Annibal Caro's "Eneide" (Prassi Ecdotiche della Modernità Letteraria, 2018)
After sketching a brief profile of Monti as a reader, in this paper is provided the edition of a series of unpublished notes by Monti, written on a working copy of the Sonzogno edition of the Eneide by Annibal Caro (Triv. G 715), witnessing a previous version of the text. The analysis of the notes turns out to be an opportunity to reconstruct the history of the edition and of the philological methods to which it conforms.
Keywords: Vincenzo Monti; Annibal Caro; Eneide; notes; annotations; Sonzogno; Vincenzo Ferrario